Pengaruh Media Pembelajaran Inovatif Koper Edukasi Asean terhadap Hasil Belajar Siswa - Purwandari, Susi (Jurnal Didaktika Pendidikan Dasar, 2019)
The aims of this research are to explain the Koper Edukasi ASEAN as an innovative media about the stages of children’s cognitive development, to explain how to use it in civics learning, and to describe the magnitude of improvement in student learning outcomes after using innovative media Koper Edukasi ASEAN in civics learning in 6th grades of SDN Bantal in the school year 2017/2018. The innovative media of the Koper Edukasi ASEAN is used in civics learning about ASEAN in three meetings. At each meeting, learning uses the Koper Edukasi ASEAN media with different materials. The method used in this research is the quasi-experimental method. The form of quasi-experimental design used is time-series design. The use of the Koper Edukasi ASEAN is adjusted to the syntax which consists of five stages, i.e. group formation, group assignment work, presentation of the results of group discussions, discussion of the results of group discussions, and awards. The application of the syntaxes is complemented by how it is adjusted according to the civics learning implementation plan on ASEAN materials. The results of this research show that the use of Koper Edukasi ASEAN increases student’s learning outcomes, proven from the class average value which was originally 66 has increased to 84, which means it has increased 18 (21%). The Learning completeness which was originally 60% has increased to 100%, which means it has increased by 40%.